Characteristics of teachers in the basic education of the city of MachalaCharacteristics of teachers in the basic education of the city of Machala - Espinoza Freire, Eudaldo Enrique (Transformación, 2024)
Objective: The article is derived from a descriptive study that aimed to characterize the teacher of basic education in the city of Machala.Methods: The author followed a quantitative qualitative methodology; based on the bibliographic, analytical-synthetic, phenomenological and statistical review methods applied to a sample of 90 (70.3%) randomly selected students from a population of 128 third-level students, from the basic education career, of the University Machala Technique (UTMach), inserted in pre-professional practice.Results: The findings allowed to describe the profile of teachers of primary education, showing a tendency towards the attributes of teachers of the 21st century, although still limited in the competences of digital culture, creativity and listening, understanding, support and empathy, aspects to keep in mind for their training and improvement.Conclusions: The author arrived at the conclusion that basic education teachers need to acquire technological skills and use them efficiently; develop the ability to help, design, lead, direct and plan learning environments; as well as focus their attention on the student.
Keywords: Primary education; teacher education; teacher qualifications; teacher evaluation